2020
DOI: 10.3390/en13051288
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption on Dairy Farms: A Review of Monitoring, Prediction Modelling, and Analyses

Abstract: The global consumption of dairy produce is forecasted to increase by 19% per person by 2050. However, milk production is an intense energy consuming process. Coupled with concerns related to global greenhouse gas emissions from agriculture, increasing the production of milk must be met with the sustainable use of energy resources, to ensure the future monetary and environmental sustainability of the dairy industry. This body of work focused on summarizing and reviewing dairy energy research from the monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 49 publications
(146 reference statements)
0
35
0
Order By: Relevance
“…Precooling milk via water through a plate cooler may reduce milk-cooling energy requirements by up to 50% [56,57]. However, careful consideration must be given to the financial and environmental impact of this utilization of water, as discussed by Murphy et al [58].…”
Section: Dairy Water Analysesmentioning
confidence: 99%
“…Precooling milk via water through a plate cooler may reduce milk-cooling energy requirements by up to 50% [56,57]. However, careful consideration must be given to the financial and environmental impact of this utilization of water, as discussed by Murphy et al [58].…”
Section: Dairy Water Analysesmentioning
confidence: 99%
“…In the particular case of this industry, a growth of 22% in milk production is expected for the 2018-2027 period [16], and 19% in its consumption by 2050 ( [17], cited in [7]). From the energy consumption perspective, it is added the fact that electrical energy represents one of the items with the highest consumption for both conventional and organic dairy farms, representing 14% and 24% of total primary energy consumption, respectively, according to [18]. Considering the above, the incentives for photovoltaic system installation, particularly in the dairy industry, are considerable.…”
Section: Pv Systems On Daily Farmsmentioning
confidence: 99%
“…us, the battery state of charge SOC is calculated from equation (18), considering the remaining energy, where SOC a is the SOC at the moment immediately before the current period, that is, the previous hour, considering a simulation on an hourly basis. Any excess energy generated by the system is dissipated and is represented by E loss , given by equation (19).…”
Section: Stochastic Pv Sizing Simulation Modelmentioning
confidence: 99%
“…Energy consumption is one of the most important production factors in German dairy farming. Besides environmental impacts, the aspects of energy consumption in dairy farming are economic impacts due to increasing energy costs [1]. In recent decades the increase in energy costs in agriculture is mainly due to rising energy prices, but also due to increased mechanisation and automatisation on the farms [2].…”
Section: Introductionmentioning
confidence: 99%
“…Sales of automatic milking systems have risen in recent years [4]. A review by Shine et al [1] found milking the largest consumer of electric energy, while the main consumption could not be assigned to a certain component. According to Pommer et al [5], in dairy farming, 56% to 70% of the total energy consumption is used for milking and milk cooling.…”
Section: Introductionmentioning
confidence: 99%